Preliminary characterization of a novel form of progressive retinal atrophy in the German Spitz dog associated with a frameshift mutation in GUCY2D - Bortolini, Mariza; Winkler, Paige A.; Moreno, Juan Carlos Duque; Sato, Mario Teruo; Guareschi, Bianca Luiza Valduga; Petersen‐Jones, Simon M.; Montiani‐Ferreira, Fabiano (Veterinary ophthalmology, 2023)
Objective To describe the clinical, preliminary electroretinographic and optical coherence tomography features of a newly identified form of progressive retinal atrophy (PRA) in German Spitzes, and identify the causal gene mutation. Animals Thirty‐three client‐owned German Spitz dogs were included. Procedures All animals underwent a full ophthalmic examination, including vision testing. In addition, fundus photography, ERG, and OCT were performed. A DNA‐marker‐based association analysis was performed to screen potential candidate genes and the whole genomes of four animals were sequenced. Results Initial fundus changes were pale papilla and mild vascular attenuation. Oscillatory nystagmus was noted in 14 of 16 clinically affected puppies. Vision was impaired under both scotopic and photopic conditions. Rod‐mediated ERGs were unrecordable in all affected dogs tested, reduced cone‐mediated responses were present in one animal at 3 months of age and unrecordable in the other affected animals tested. Multiple small retinal bullae were observed in three clinically affected animals (two with confirmed genetic diagnosis). OCT showed that despite loss of function, retinal structure was initially well‐preserved, although a slight retinal thinning developed in older animals with the ventral retina being more severely affected. Pedigree analysis supported an autosomal recessive inheritance. A mutation was identified in GUCY2D, which segregated with the disease (NM_001003207.1:c.1598_1599insT; p.(Ser534GlufsTer20)). Human subjects with GUCY2D mutations typically show an initial disconnect between loss of function and loss of structure, a feature recapitulated in the affected dogs in this study. Conclusion We identified early‐onset PRA in the German Spitz associated with a frameshift mutation in GUCY2D.